Implementasi Ajaran Tasawuf terhadap Pengendalian Emosi - Bilqis Rizma Ahmadia (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss the implementation of Sufism teachings on emotional control. This study uses a qualitative approach by applying a descriptive-analytical method. The formal object of this research is the teachings of Sufism, while the material object is emotional control. The results of the research and discussion show that the implementation of Sufism's teachings on emotional control can be done by means of dhikr, reading the Koran, performing ablution, even seclusion, if done in the right way then emotions can be easily controlled. This research concludes that the teachings of Sufism can help oneself to control the emotions that exist in every human being. This study recommends that Islamic religious institutions develop the implementation of tasawuf teachings as a way of controlling emotions so as to create an emotionally healthy generation in Indonesia.